PENGARUH TEMPERATUR DAN PENAMBAHAN METANOL PADA PROSES ESTERIFIKASI - TRANSESTERIFIKASI TERHADAP SIFAT-SIFAT MINYAK NYAMPLUNG - Woesono, Hastanto Bowo; Webliana, Kornelia (Fakultas Kehutanan Institut Pertanian STIPER Yogyakarta, 2011)
The problem which has to be solved when using nyamplung oil (Calophyllum inophyllum) as an alternative fuel is the excessive content of free fatty acid in the oil. One way of reducing the free fatty acid in the oil is by esterification and tranesterification process. Hence, the research is conducted to identify the effect of temperature and methanol addition on the esterification and transesterification processes on the nature of nyampung oil and to assess the composing component of nyamplung oil. The research was conducted in the laboratory of Forest Yield Technology and central laboratorium of INSTIPER. The steps included extraction, deguming, esterification I, esterification II and transesterification with the temperature var iation of 60° C, 80° C, and 100° C and the mol comparison of nyamplung oil of 4:1, 5:1 and 6:1, and the examined parameters were water content, viscosity, acid level, soap level, free fatty acid content and iod level. The result indicated that the temperature treatment and methanol addition significantly affected the nature of nyamplung oil after the tranesterification. The analysis of nyamplung oil nature after the esterification I and esterification II indicated that the water contents were 0.38 and 0.21 %, the densities were 0.9630 and 0.9325 g/ml, the viscosities were 110 and 74.5 cP, the acid levels were 58.6893 and 31, 4359 KOH/g. the contents of free fatty acid were 29.5016 and 15.8017, the soaping levels were 192, 4127 dan 180, 2165 mg KOH/g, the iod levels were 68.7259 and 65. 9123 mg/g with the appearance of esterification I of dark and aqueous and esterification 11 reddish and aqueous. the nature of nyamplung oil after the transesterification process was that the water content was 0.1501%, the density was 0.8832 Wml, the viscosity was 51.1296 eP, the acid level was 9.8935 KOH/g, the free fatty acid content was 5.0168 %, the soaping level was 172.9321 KOH/g, the iold level was iod 77.4985 mg/g, with the appearance of yellow and aqueous. Keywords: Temperature, methanol comparison, transesterification process, nyamplung oil properties